Cognitive mapping of chief executive officers' minds: confronting Chinese global competitiveness. (20th May 2009) - Foo, Check Teck; McKiernan, Peter; Wong, James
In Western philosophy on epistemology, there has long been the traditional divide between what is a priori vs. a posteriori. This is taken as the starting point for a conceptual framing of an empirically grounded inquiry into the minds of Indian chief executive officer (CEOs) about Chinese strategic thinking. The objective of this a posteriori experimentation is to cross culturally map Indian CEOs' knowledge – broadly defined as understandings, doubts, responses, surprises, concerns, beliefs and values, when they are put face-to-face with rapidly rising Chinese competitive pressures. To provide the focus of inquiry, the author uses the precepts of the 2, 500 years old Art of War by Sun Tzu as experimental parameterisation of knowledge concerning Chinese competitive, strategic thinking. From the results of experimentation, the first and main author then produces a cognitive map that yields intriguing insights to the mental state of CEOs' knowing and concerning about Chinese strategy.